1. First she needs to find the inverse function of f(x)= (2x+4)/3

2. Switch the x and y variables around and to get the inverse function y=(3x-4)/2 Y= (2x+4)/3

Now she has to solve for X

1: Flip the equation.

2: Add (-4)/3 to both sides.

3: Divide both sides by 2/3.

1. Y= (2x+4)/3

2. 3y=2x+4

3. 3y-4=2x

(3y-4)/2=X

She now has "x =" so switch X AND Y FOR THE INVERSE y=(3x-4)/2 Solve x=6 (x=number of inches) y=(3x-4)/2 y=(3(6)-4/2 y=7 Neveah's hair would grow 6 inches in 7 months. (7 is the Y-intercept)

7=(3(6)-4)/2